Transportation Company Value Determinants during the Covid-19 Pandemic - Inggit Setiyadi; Ranila Suciati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Kind of research is quantitative with the aim of examines the variables that affect the value of transportation companies during the Covid-19 pandemic. A total of 23 transportation companies listed on the Indonesia Stock Exchange to be used as research samples with the determination of the sample that is simple random sampling. The hypothesis test used in this study is panel data regression using the E-views 12.0 program and using a significance level of 5%. The results obtained are as follows (1) there is a significant effect of capital structure on the value of transportation companies during the Covid-19 pandemic, (2) there is a significant effect of profitability on the value of transportation companies during the Covid-19 pandemic, and (3) there is no significant effect of interest rates the value of transportation companies during the Covid-19 pandemic.